2015
DOI: 10.4238/2015.july.13.2
|View full text |Cite
|
Sign up to set email alerts
|

Genetic diversity in Tunisian populations of faba bean (Vicia faba L.) based on morphological traits and molecular markers

Abstract: ABSTRACT. Genetic diversity within Vicia faba L. is key to the genetic improvement of this important species. In this study, morphological traits and RAPD molecular markers were used to assess the levels of polymorphism across 12 Tunisian populations, three major and nine minor from different locations. Analysis of morphological traits indicated that the three major populations showed significant differences and the nine minor populations exhibited considerable variation for most traits. The grain yield of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
2

Year Published

2017
2017
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 23 publications
1
9
2
Order By: Relevance
“…The average number of alleles per locus (5.87) was higher compared to SSR (1.6) and SSAP markers (1.68) (Ouji et al 2012) and the lowest compared to RAPD (31.0) and ISSR (10.9) (Backouchi et al 2015;Asfaw et al 2018); the results were supported by Abid et al (2015) who showed the average number of alleles was 5.94 and ranged from 2 to 10. The percentage of polymorphic alleles was 97.9% and was higher compared to TRAP 55.2%, RAPD 75.96%, and ISSR 85.5% (Kwon et al 2010;Elshafei et al 2011;Backouchi et al 2015;Asfaw et al 2018. ); they reported that using 19 SRAP primers combined with six Yucca genotypes, a total of 65 alleles amplified, 72.3% were polymorphic alleles with 7.2 alleles per primer.…”
Section: Srap Analysismentioning
confidence: 91%
See 1 more Smart Citation
“…The average number of alleles per locus (5.87) was higher compared to SSR (1.6) and SSAP markers (1.68) (Ouji et al 2012) and the lowest compared to RAPD (31.0) and ISSR (10.9) (Backouchi et al 2015;Asfaw et al 2018); the results were supported by Abid et al (2015) who showed the average number of alleles was 5.94 and ranged from 2 to 10. The percentage of polymorphic alleles was 97.9% and was higher compared to TRAP 55.2%, RAPD 75.96%, and ISSR 85.5% (Kwon et al 2010;Elshafei et al 2011;Backouchi et al 2015;Asfaw et al 2018. ); they reported that using 19 SRAP primers combined with six Yucca genotypes, a total of 65 alleles amplified, 72.3% were polymorphic alleles with 7.2 alleles per primer.…”
Section: Srap Analysismentioning
confidence: 91%
“…The evaluation of genetic variability among faba bean landraces using agro-morphological and molecular markers revealed that sequence-related amplified polymorphism (SRAP) and amplified fragment length polymorphism (AFLP) markers are used to determine the genetic variability among genotypes (Ammar et al 2015;Backouchi et al 2015;Abid et al 2015;Rebaa et al 2017;Alemu et al 2018). AFLP markers and combined SRAP are considered to be remarkably beneficial for the evaluation of genetic variability at the molecular level.…”
Section: Introductionmentioning
confidence: 99%
“…These data suggested that Tunisian faba bean populations are polymorphic, providing a large number of alleles within populations. In general, a relatively high genetic diversity was found in Tunisian faba bean germplasm (Ouji et al 2012;Backouchi et al 2015). Many factors act to influence population genetic diversity including mating system, gene flow and seed dispersal, geographic range as well as natural selection (Amos and Harwood 1998).…”
Section: Discussionmentioning
confidence: 99%
“…In general, faba bean seeds had the highest value of 100-seed weight (range 21-196 g) and lentils and grass peas the lowest (respective ranges 1.5-6 g and 6-37 g). Indeed, seed weight has been shown to be a morphological parameter that varies greatly among faba bean germplasms (Yahia et al 2012;Backouchi et al 2015). The mean hydration capacity for all four species varied in the range 100-120%, and the percentage of unhydrated seeds was highest in faba bean germplasm, reaching 21%.…”
Section: Physico-chemical and Pasting Characteristics Of The Germplasmentioning
confidence: 99%